Cinnamic acid derivatives: inhibitory activity against Escherichia coli β-glucuronidase and structure–activity relationships. (1st January 2020) - Li, Xing-Nuo; Hua, Lu-Xia; Zhou, Tao-Shun; Wang, Ke-Bo; Wu, Yuan-Yuan; Emam, Mahmoud; Bao, Xiao-Ze; Chen, Jun; Wei, Bin
Abstract: Gut microbial β -glucuronidase (GUS) is a potential therapeutic target to reduce gastrointestinal toxicity caused by irinotecan. In this study, the inhibitory effects of 17 natural cinnamic acid derivatives on Escherichia coli GUS (EcGUS) were characterised. Seven compounds, including caffeic acid ethyl ester (CAEE), had a stronger inhibitory effect (IC50 = 3.2–22.2 µM) on EcGUS than the positive control, D-glucaric acid-1, 4-lactone. Inhibition kinetic analysis revealed that CAEE acted as a competitive inhibitor. The results of molecular docking analysis suggested that CAEE bound to the active site of EcGUS through interactions with Asp163, Tyr468, and Glu504. In addition, structure–activity relationship analysis revealed that the presence of a hydrogen atom at R1 and bulky groups at R9 in cinnamic acid derivatives was essential for EcGUS inhibition. These data are useful to design more potent cinnamic acid-type inhibitors of EcGUS.